Do student nurses experience Imposter Phenomenon? An international comparison of Final Year Undergraduate Nursing Students readiness for registration. (5th July 2016) - Christensen, Martin; Aubeeluck, Aimee; Fergusson, Diana; Craft, Judy; Knight, Jessica; Wirihana, Lisa; Stupple, Ed
Abstract: Background: The transition shock or Imposter Phenomena sometimes associated with moving from student to Registered Nurse can lead to feelings of self‐doubt and insecurity especially with the increased expectations and responsibilities that registration brings. Aim: The aim of this study was to examine the extent at which imposter phenomenon is evident in four final year nursing student cohorts in Australia, New Zealand and the UK. Design: A survey design. Settings: The study took place at four higher education institutes – two metropolitan campuses and two regional campuses between October 2014 – February 2015 in Australia, New Zealand and the UK. A sample of 223 final year nursing students undertaking nationally accredited nursing programmes were approached. Results: Each cohort exhibited mild to moderate feelings of Imposter Phenomena. A positive weak correlation between imposter phenomena and preparedness for practice was found. The New Zealand cohort scored higher than both the Australian and UK cohorts on both feelings of imposterism and preparedness for practice. Conclusions: Nursing students possess internalized feelings which suggest their performance and competence once qualified could be compromised. There is some speculation that the respective curriculums may have some bearing on preparing students for registration and beyond. It is recommended that educational programmes designed for this student cohort should be mindful of this internal conflict and potential external hostility.